A New Approach Combining Analytical Methods for Workplace Exposure Assessment of Inhalable Multi-Walled Carbon Nanotubes. Issue 7 (11th July 2017) - Tromp, Peter C; Kuijpers, Eelco; Bekker, Cindy; Godderis, Lode; Lan, Qing; Jedynska, Aleksandra D; Vermeulen, Roel; Pronk, Anjoeka
Abstract: To date there is no consensus about the most appropriate analytical method for measuring carbon nanotubes (CNTs), hampering the assessment and limiting the comparison of data. The goal of this study is to develop an approach for the assessment of the level and nature of inhalable multi-wall CNTs (MWCNTs) in an actual workplace setting by optimizing and evaluating existing analytical methods. In a company commercially producing MWCNTs, personal breathing zone samples were collected for the inhalable size fraction with IOM samplers; which were analyzed with carbon analysis, inductively coupled plasma mass spectrometry (ICP-MS) and scanning electron microscopy/energy dispersive X-ray spectroscopy (SEM/EDX). Analytical methods were optimized for carbon analysis and SEM/EDX. More specifically, methods were applied and evaluated for background correction using carbon analyses and SEM/EDX, CNT structure count with SEM/EDX and subsequent mass conversion based on both carbon analyses and SEM/EDX. A moderate-to-high concordance correlation coefficient (RC ) between carbon analyses and SEM/EDX was observed [RC = 0.81, 95% confidence interval (CI): 0.59–0.92] with an absolute mean difference of 59 µg m −3 . A low RC between carbon analyses and ICP-MS (RC = 0.41, 95% CI: 0.07–0.67) with an absolute mean difference of 570 µg m −3 was observed. The large absolute difference between EC and metals is due to the presence of non-embedded inhalable catalyst particles, as a result of which MWCNT concentrations were overestimated. Combining carbon analysis and SEM/EDX is the most suitable for quantitative exposure assessment of MWCNTs in an actual workplace situation.